2015
DOI: 10.1080/01457632.2015.1010921
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Micro Pin-Fin Shape on Thermal and Hydraulic Performance of Micro Pin-Fin Heat Sinks

Abstract: Single micro pin-fin configurations having the same chord thickness/diameter but different shapes are numerically modeled to assess their heat transfer and hydraulic performances for Reynolds number values changing between 20 and 120. The configurations are three-dimensionally modeled based, and their heat transfer performances are evaluated using commercially available software COMSOL Multiphysics 3.5a. Navier-Stokes equations and continuity and energy equations are solved under steady-state conditions for si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(25 citation statements)
references
References 38 publications
4
21
0
Order By: Relevance
“…Numerous studies on micro pin fin arrays have also been performed, made possible by new manufacturing techniques such as diffusion bonding, stereolithography, chemical etching and LIGA [11]. Some of the studies were motivated by an interest in 1X scale performance for gas turbine airfoil skin cooling [12] and others were focused on small electronics cooling [13][14][15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies on micro pin fin arrays have also been performed, made possible by new manufacturing techniques such as diffusion bonding, stereolithography, chemical etching and LIGA [11]. Some of the studies were motivated by an interest in 1X scale performance for gas turbine airfoil skin cooling [12] and others were focused on small electronics cooling [13][14][15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the flow velocity increases, the force exerted by fluid from, pin fin surface increases leading to flow separation around pin fin and wake formation. Increase in flow velocity promotes flow separation leading to increase in larger wake zone [3]. From the stream line contour it is very clear that secondary vortices are formed for both MCHS- SPF and MCHS-CPF, This may be due to the influence of turbulence promoting flow separation at low Reynolds number.…”
Section: Maximum Thermal Resistancementioning
confidence: 95%
“…The concept of micro channel was first proposed by Tuckerman and Pease [1], Shafeie et al [2] numerically studied the performance of heat sink with staggered and oblique arrangement and observed that oblique pin fin performs better compared to staggered for a given pumping power. Hydrodynamic and heat transfer characteristics have been explored numerically for heat sink with pin fin structures by Turker Izci et al [3], Hasan et al [4] numerically compared hydrodynamic and heat transfer characteristics of micro pin fin heat sink of different shapes using water and Nano fluids. Sohail et al [5] proposed pin fin array of various shapes to reduce maximum surface temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Aero-and space-based electronic applications that demands high-flux heat dissipation entails stringent requirement on weight and space occupation in the meanwhile [1] [2].…”
Section: Introductionmentioning
confidence: 99%